Ion-migration and carrier-recombination inhibition by the cation-π interaction in planar perovskite solar cells - Sagar Jain (Organic Electronics, 2019)
In organic-inorganic hybrid perovskite solar cells, migration of intrinsic ions (e.g., MA+, Pb2+, I−) have a significant impact on the current-voltage hysteresis and stability of devices. Here, N, N′-diphenyl-1, 1′-biphenyl-4, 4′-diamine (NPB) was introduced into MAPbI3 perovskite layer to facilitate the stability of perovskite film and improved the efficiency of planar perovskite solar cells (PSCs). The results suggest that migration of intrinsic ions are inhibited effectively by cation-π interaction between NPB and MA+, and lead to reduce intrinsic defects in perovskite films, which is benefit for the stability of devices. Lewis basicity of NPB enhances the crystallization, passivates the perovskites films and addresses the issue of low electron extraction efficiency. Consequently, solar cells made using NPB modified MAPbI3 resulted hysteresis-free, enhanced power conversion efficiency of 19.22% with improved stability.